A Multimodal Course Design for Intercultural Business Communication. Issue 3 (2nd July 2020) - Wang Guénier, Amily Dongshuo
ABSTRACT: This study presents a course design that integrates multimodal sounds, pictures, videos, student presentations, guest speakers, and group work into a multimodal course to enhance intercultural communication competence into a high-profile business training course. The course is tailor-made for 488 managers and staff in one of the world's top 10 banks whose branch is based in London. Innovative experiential techniques are embedded in the course to meet their professional needs. The evaluation from the participants suggested that the course was highly useful and challenging, which produced a positive impact on the trainees' intercultural awareness and empathy in terms of more affective commitment, better behavioral performance and enhanced cognitive curiosity in intercultural business communication (IBC). The innovative ideas of the course design, examples of good practice and integrated multimodal pedagogy have paved the way for other colleagues designing and delivering similar courses.